Analisis Bauran Pemasaran dalam Meningkatkan Daya Beli Konsumen : Studi Kasus pada Batik Mirabella di Kecamatan Simpang Pulai Jambi - Dina Widian Putri; Novi Mubyarto; Mohammad Orinaldi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
The Marketing Mix is ​​known as 4P and has components, namely product, price, place and promotion. Mirabella Batik Shop, Jambi City is a business that operates in the field of selling genuine Jambi batik and batik from outside Jambi or from Java. Various types of batik materials such as handloom, silk, semi-silk, sanwos, cotton, semi-written. And types of motifs such as Angso duo, Kapal Sangat, Durian Pecah, Tampuk Manggis and Kopi. This Mirabella batik shop is very good with good quality products. The problem faced by the Mirabella Batik Shop in Jambi City is that sales have decreased in sales volume, the marketing strategy looks good but it is difficult to attract consumers. Mirabella Batik Shop, apart from using social media to promote its products, the batik shop also uses a Word of Mouth (WOM) system, which can be called word-of-mouth promotion. This research aims to determine the application of marketing mix analysis in attracting consumer buying interest in Mirabella Batik, Jambi City. The location of this research is located on Jalan Sultan Agung No. 21 Rt 16/02 Kel. Pure District. Telanalpura Simpang Pulai, Jambi City. This research is a qualitative descriptive research, because it aims to describe the conditions and phenomena in the field at the Mirabella Batik Shop, Jambi City and uses data collection techniques in this research, namely interviews, observation and documentation. The data source in the research is primary data from interviews with shop owners, shop employees and consumers. And secondary data from books and journals. The research results show that there are 4 marketing mixes carried out by the Mirabella Batik Shop in Jambi City, namely Product, Price, Place and Promotion. The influence on the Marketing Mix at the Mirabella Batik Shop, Jambi City, the product quality is very good, but attracting consumers is very difficult due to competitiveness in other shops.